Realism and Climate Change: Evaluating Great Powers' Foreign Policies in a Warming World (Journal of Asian Development Studies, 2023)
This article investigates the realism in international relations and the unyielding global issue of climate change by assessing the foreign policies of great powers in a warming world. The review resolves the focal inquiry of how realist standards impact the methodologies of great powers, like the US, China, and the European Union, in answering climate change difficulties. This research utilizes a blended strategies approach, consolidating subjective investigation of strategy reports, settlements, and master interviews. Our findings demonstrate that realist standards, including personal responsibility, power legislative issues, and state-driven conduct, assume a huge part in molding the environmental strategies of these great powers. Prominently, the US will, in general, focus on public interest and monetary development in its environmental strategies, while China offsets ecological worries with power gathering. In the meantime, the European Union features a more helpful methodology that aligns with the realist idea of organizations as devices for power projection. This examination adds to a superior comprehension of how realism illuminate environmental discretion in a multipolar world. The ramifications of this study stretch out to the domains of international relations theory and work on, featuring the requirement for a realist focal point in breaking down and tending to the complicated and interconnected international difficulties presented by climate change in the twenty-first 100 years.